1986
DOI: 10.1039/p19860000815
|View full text |Cite
|
Sign up to set email alerts
|

Higher-carbon sugars. Part 1. The synthesis of some octose sugars via the osmylation of unsaturated precursors

Abstract: The stereochemical outcome of the osmium tetraoxide oxidation of a number of unsaturated carbohydrate derivatives, including (€) -and (Z) -6,7-dideoxy-l,2 : 3,4-di-~-isopropylidene-a-o-ga/acto-oct-6-enopyranose (6) and (9), methyl (Z) -6,7 -dideoxy-1,2 : 3,4-di -0-isopropylidene-a-D-galacto-oct -6-enopyranuronate ( 8 ) , and 7,8-dideoxy-1,2 : 3,4-di-0-isopropylidene-a-D-glycero-~-ga/acto-oct-7 -enopyranose (1 0), has been examined. Such oxidations resulted in the preparation of the synthetically usef u I octos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…96 For example, in 1970 Szarek reported that treatment of olefin 83 with aqueous potassium permanganate gave diol 84 as the sole product.97 As shown in Table 7, entry 2, exclusive "anti" selectivity was obtained for catalytic osmylation. 47 There have appeared two additional comparison studies: both KMnC>4 and OSO4 dihydroxylations of olefin 85 (Table 11, entry 3) gave the anti diol in 3:1 selectivities. Similar results were obtained for olefin 86 (from Table 12, entry 5).…”
Section: Double Stereodifferentiationmentioning
confidence: 99%
“…96 For example, in 1970 Szarek reported that treatment of olefin 83 with aqueous potassium permanganate gave diol 84 as the sole product.97 As shown in Table 7, entry 2, exclusive "anti" selectivity was obtained for catalytic osmylation. 47 There have appeared two additional comparison studies: both KMnC>4 and OSO4 dihydroxylations of olefin 85 (Table 11, entry 3) gave the anti diol in 3:1 selectivities. Similar results were obtained for olefin 86 (from Table 12, entry 5).…”
Section: Double Stereodifferentiationmentioning
confidence: 99%
“…29 Anomalous Z selectivity depending on substrate and solvent is also reported. [30][31][32] The reaction of 1a and b 40 C proceeded with high Z stereoselectivity (76%; 2a : 3a ¼ 87 : 13) and (89%; 2b : 3b ¼ 83 : 17), respectively (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the 2-halocyanoacetate procedure,2o a trans-bromohydrin (36; Scheme 3), prepared from an alkene, is esterified with cyanoacetic acid to give the 2-halocyanoacetate (37), and the latter is treated with sodium hydride to give, via the enolate anion, a cyanoketene acetal (38). Acid hydrolysis of the latter, followed by deesterification with base of the diol monocyanoacetate so-formed gives diol (39).…”
Section: Methods Involving Halohydrin Esters As Intermediatesmentioning
confidence: 99%